Common fixed points for multivalued mappings in ordered partial metric space - Nazari, Esmaeil; Mohitazar, Najmeh (International Journal of Applied Mathematical Research, 2015)
In the present work, we establish some common fixed point results for a pair of weakly isotone increasing set-valued mappings in a ordered complete partial metric space.